High time for government action to make the OECD Guidelines a force for sustainable FDI - Joseph M. Wilde-Ramsing; Marian G. Ingrams (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
FDI can be responsible only if it is accountable to workers and communities negatively impacted by investments and the OECD Guidelines for Multinational Enterprises should ensure accountability for victims of corporate misconduct. However, until the OECD's complaint mechanism is significantly reformed, victims will lack effective access to remedy.
Keywords: 330